A review of machine-tool vibration and its influence upon surface generation in ultra-precision machining. (April 2015) - Zhang, S.J.; To, S.; Zhang, G.Q.; Zhu, Z.W.
Abstract: Vibration in ultra-precision machining (UPM) is an intrinsic physical phenomenon, which is a key factor influencing surface generation. With a focus on passive vibration, this paper reviews the latest research into vibration characteristics and the effect of vibration on surface generation in UPM. The opportunities and challenges facing researchers are also discussed and suggestions are made for future related studies. It is found that active vibration can possibly be employed to improve surface quality influenced by passive vibration in UPM. Graphical abstract: Highlights: The latest investigation into vibration and surface generation in UPM is reviewed. The opportunities and challenges facing academia are proposed for future related studies. Active vibration can possibly improve surface quality degraded by passive vibration in UPM.